2007
DOI: 10.1243/09544100jaero148
|View full text |Cite
|
Sign up to set email alerts
|

Damage detection in composites using optical fibre sensors

Abstract: Optical fibre sensors (OFSs) are promising as tools for damage and structural health monitoring (SHM) of aerospace composite structures. Hence, many researchers have conceived various kinds of OFSs. First, a brief summary of OFSs used for composites is presented. Then, the authors' studies on the small-diameter fibre Bragg grating (FBG) sensors for damage monitoring and SHM of composite structures are described. The authors and Hitachi Cable, Ltd have developed a small-diameter optical fibre and its FBG sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 65 publications
0
39
0
Order By: Relevance
“…Unidirectional glass fibres with a density of 1200 g/cm 3 were used for composite production, as the effect of FBG embedment in the composite is assumed to be negligible in higher density of reinforcement fibres. The composite was produced using the cold infusion method, with vacuum bagging technique.…”
Section: Composite Productionmentioning
confidence: 99%
“…Unidirectional glass fibres with a density of 1200 g/cm 3 were used for composite production, as the effect of FBG embedment in the composite is assumed to be negligible in higher density of reinforcement fibres. The composite was produced using the cold infusion method, with vacuum bagging technique.…”
Section: Composite Productionmentioning
confidence: 99%
“…Reference [6] found that the FBG spectrum was sensitive to the delamination propagation behavior of composite materials. The spectrum was split into two peaks dependent on the strain gradient which was caused by edge delamination.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous paper, published in 2007 [5], presented the development of small-diameter optical fibers and their fiber Bragg grating (FBG) sensors. The paper showed several techniques for detecting composite damage and gave a summary of the Japanese national project on optical-fiber-based SHM for feasible applications in aerospace composite structures.…”
Section: Introductionmentioning
confidence: 99%